2012
DOI: 10.1111/j.1399-6576.2012.02721.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological normalization of circulation after acute brain death

Abstract: Pharmacological substitution of pituitary gland function, blockade of peripheral catecholamine neuronal reuptake and low doses of catecholamines normalize circulation in decapitated pigs throughout a 24-h observation period, whereas untreated decapitated pigs all develop severe circulatory collapse within 12 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 13 publications
5
45
1
1
Order By: Relevance
“…This led Steen et al to propose a collection of hormones which promoted hemodynamic stability in decapitated animals, including epinephrine, thyroxine, desmopressin, and cortisol; similar results were obtained by Hing et al. 22,23 Keeping with these principles, the OCS includes constant infusion of TransMedics Maintenance Solution, which includes insulin, glucocorticoids, bicarbonate, adenosine, and low dose epinephrine. 9,10,24 However, given that preservation time appears to remain limited, the current list of OCS perfusate ingredients must lack essential components.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This led Steen et al to propose a collection of hormones which promoted hemodynamic stability in decapitated animals, including epinephrine, thyroxine, desmopressin, and cortisol; similar results were obtained by Hing et al. 22,23 Keeping with these principles, the OCS includes constant infusion of TransMedics Maintenance Solution, which includes insulin, glucocorticoids, bicarbonate, adenosine, and low dose epinephrine. 9,10,24 However, given that preservation time appears to remain limited, the current list of OCS perfusate ingredients must lack essential components.…”
Section: Discussionmentioning
confidence: 76%
“…6,18,20 Blood perfusion alone is inadequate, however, as the isolated perfused heart tends to emulate the loss of viability and vascular tone seen in the cardiovascular collapse of brain-dead humans and animals. 11,21,22 It is likely that circulating metabolic substrates and hormones are necessary to maintain organ integrity. This led Steen et al to propose a collection of hormones which promoted hemodynamic stability in decapitated animals, including epinephrine, thyroxine, desmopressin, and cortisol; similar results were obtained by Hing et al.…”
Section: Discussionmentioning
confidence: 99%
“…6 This theory is supported by clinical observation and experimental paradigms suggesting that neurologic regulation may be important for organ viability and vascular tone. 18,19 Dr. Steen’s group has proposed a cocktail of hormones that may be important in regulating vascular tone, and were able to use this cocktail to promote hemodynamic stability in decapitated animal experiments. Others have shown that hormone therapies can improve myocardial function after brain death in similar animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that hormone therapies can improve myocardial function after brain death in similar animal experiments. 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive summary of the pathophysiological evolution of the BD patient is found in [4]. An in vivo porcine study presented in [5], shows promising results of a novel pharmacological therapy aimed at achieving hemodynamic stability in BD patients. The therapy consists of intravenous infusion of a drug cocktail, consisting of noradrenaline (0.02 mg/ml), adrenaline (0.02 mg/ml), cocaine (0.02 mg/ml), thyroid hormones T3 (0.006 mg/ml) and T4 (0.006 mg/ml), anti-diuretic hormone (desmopressin) (0.72 µg/ml 1 ), and cortisol (6 mg/ml).…”
Section: Introductionmentioning
confidence: 99%